A study about physical fitness can improve learning performance among young adults / Siti Khadijah Muhammad Zahid - Muhammad Zahid, Siti Khadijah (2019)
Physical fitness is the exercise that has been shown effectively to body function and brain function. It also helps to improve learning performance among young adults. Fitness it is not only thing with sport. It also can be use like daily routine to increase lung capacity and give us strength to our muscle. It also helps to reduce stress and get a better sleep. Fitness help much to prevent getting heart disease. Moreover, fitness also lubricates the joints and reduce joint pain and stiffness. Fitness or physical activity strengthen the muscle and improve balance and coordination. On the research study the researcher using the quantitative as the method approach to get the information by collecting data. The quantitative is based on the survey about effects of physical fitness for young adults health. Analysis of the data obtained indicates that respondents are less aware of the effects that can be obtained from physical fitness. The goal is to create some Info Graphic poster design for this study and want to share knowledge with others in the future.